Impact of micropulsed ultrasound power settings on the efficiency and chatter associated with lens‐fragment removal. Issue 6 (June 2015) - Garff, Kevin; Jensen, Jason D.; Cahoon, Judd; Gupta, Isha; Stagg, Brian; Zaugg, Brian E.; Barlow, William R.; Olson, Randall J.
Abstract : Purpose : To determine the optimum power settings in micropulsed ultrasound (US). Setting : John A. Moran Eye Center Laboratories, University of Utah, Salt Lake City, Utah, USA. Design : Experimental study. Methods : Pig lenses hardened to be comparable to dense human cataracts were cut into 2.0 mm cubes and removed using micropulsed longitudinal US with previously optimized settings (6 milliseconds on and 6 milliseconds off and using a 0.9 mm 30‐degree beveled bent phaco tip). The aspiration was set at 40 mL/min and the vacuum level at 550 mm Hg. Twenty lens cubes were tested with the power set from 10% to 100% in increments of 10%. Primary outcome measures were efficiency time (time to lens removal) and chatter (number of times the lens fragment visibly bounced off the tip). Results : Efficiency time decreased with increasing power. There was a correlation between power and efficiency time ( R 2 = 0.41, P = .046), which was more substantial between 30% and 100% power ( R 2 = 0.71, P = .004). The mean number of chatter events did not differ significantly between power settings ( R 2 = 0.012, P = .1195). Conclusions : There was a 5‐fold increase in efficiency between 10% power and 20% power, which likely indicates that there is a minimum power threshold for efficient breakup of the lens. Between 20% and 100% power, there was a linear, strong, and statistically significant improvement in efficiency in these lens fragments. In addition, with micropulsed US there was little chatter or microchatter throughout the power range. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.